The Influence Of Tax Knowledge And Tax Examination On Taxpayer Compliance With Tax Sanctions As A Moderating Variable AT KPP Pratama Binjai - Suriyadi, Suriyadi; Syafrida Hani; Irfan (Cattleya Darmaya Fortuna, 2024)
The level of taxpayer compliance at KPP Pratama Binjai has decreased in 2018, 2019 and 2021. Taxpayers can be said or considered compliant if the taxpayer pays and reports the tax payable in a timely manner. This study aims to examine and analyze the effect of tax knowledge and tax audits on taxpayer compliance with tax sanctions as a moderating variable at KPP Pratama Binjai. The research method used is quantitative. This research consists of population and sample. Where the population in this study were 76,017 taxpayers registered at the Binjai City Primary Tax Service Office and the sample in this study was 100 respondents. The data analysis technique used in this study is Structural Equation Modeling-Partial Least Squares (SEM-PLS) using SmartPLS software. The results of the study show that (1) Tax Knowledge has a significant effect on Taxpayer Compliance. (2) Tax Audit has a significant effect on Taxpayer Compliance (3) Tax Sanctions significantly moderate the effect of Tax Knowledge on Taxpayer Compliance. (4) Tax Sanctions significantly moderate the effect of Tax Audit on Taxpayer Compliance. (5) Knowledge of Taxes and Tax Audit is able to explain Taxpayer Compliance of 31.5%, the remaining 68.5% is explained by other factors.